A molecular perspective on orchid development. Issue 5 (2nd September 2020) - Balilashaki, Khosro; Moradi, Shirin; Vahedi, Maryam; Khoddamzadeh, Amir Ali
ABSTRACT: Despite a common misconception that the orchid is a large family with amazing members, the fact that the orchid is the king of beauties is irrelevant. As much as this family has amazing members, its growth stages are very different. Finding the right growth paths and getting the right models for each step for such a family is impossible with the old, simple ways. Over the past two decades, orchid biologists have achieved some approach with these new methods. In the meantime, orchid genomes have been revealed and the post-genomics studies were getting more attention. This review presents the comprehensive perspective of the most recent developments and approaches on orchid research using some new molecular methods like omics technologies, with focus on developmental processes in orchids from seed formation to flower senescence. Also, the most thoroughly studied fields in orchids, i.e. floral transition and flowering, have been discussed in detail.